Floc settling characteristics of turbid water coagulated with Moringa oleifera seeds - Muyibi, Suleyman A.; Evison, Lilian M. (Gordon and Breach Science Publishers, 1999)
The results of studies into the particle aggregations and settling rates of flocs from turbid water (kaolin suspension) with turbidities varying from 50 to 550 NTU coagulated with Moringa oleifera seeds are presented. The results of the laboratory based study showed that the maximum value of the 'apparent aggregation rate', K(app), increased with increase in initial turbidity. K(app) was found to be 0.000778 for low turbidity (50 NTU) and 0.00654 for high turbidity (550 NTU). The velocity gradient for rapid mix at the maximum K(app) was found to be constant at 443/sec for all turbidities. Settling rate of floc coagulated with Moringa oleifera seed was dependent on the initial turbidity of the water sample. For water with initial turbidity of 50 NTU, 30% to 70% turbidity was removed between 60 and 210 minutes, while for high turbidity of 400 to 550 NTU, 80% to 95% turbidity removal occurred between 60 and 150 minutes.